Compliance for big brothers: An empirical analysis on the impact of the anti-trafficking protocol - Seo-young Cho; Krishna Chaitanya Vadlamannati (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
The Anti-trafficking Protocol reflects the interests of the major powers. Due to the high costs of compliance, countries will strategically select certain obligations to comply, which can satisfy the major powers with smaller costs. Among the three main obligations of the Protocol - prevention, protection and prosecution, we predict that ratification leads to compliance with the prevention policy first because prevention is less costly for member states to comply with. Therefore it is the most efficient form of compliance. We empirically test this hypothesis by employing panel data from 147 countries during the period of 2001-2009. As the theory predicts, the ratification of the Protocol has the strongest effect on the prevention policy of a member state compared to protection and prosecution. Our findings are robust to the method of estimation and the choice of variables.
Keywords: F22; F53; K33; 330; Anti-trafficking Protocol; ratification; efficient compliance; Menschenhandel; Internationales Abkommen; Normbefolgung; Rechtsdurchsetzung; Welt